CONNECTING ARTFULLY TOWARD PROMOTING THE MENTAL HEALTH OF IMMIGRANT WOMEN IN CANADA: A LITERATURE REVIEW - Motia, Maryam (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2023)
Although Canada is a popular destination for immigrants, studies of the mental health of immigrant women in Canada have shown some of migration’s potential negative impacts. These studies also showcase how social support through community engagement can improve and maintain mental health by reducing immigrant women’s hopelessness and boosting their resilience. Additionally, because it promotes self-expression and self-confidence, engagement with art can be beneficial for health outcomes. Community arts programs serve as a space for creating artworks and exchanging social support and can have a positive psychological influence on participants. For instance, community arts programs can facilitate participants’ self-expression and the development of new friendships and artistic skills. Despite the existence of diverse community arts programs across Canada, there are few Canadian-focused scholarly studies investigating how engagement with these programs may contribute to participants’ mental health. In this paper, I investigate the association between engagement with art and its mental health–related outcomes among immigrant women in Canada. To explore this relationship, I provide a review of the scholarly literature on artmaking and mental health among immigrant women in Canada and assess how community art programs may impact their mental health by offering opportunities for social support exchanges. This paper argues that community art programs foster space for promoting mental health among immigrant women, and provides suggestions for researchers, mental health professionals, settlement service providers, and policy-makers in the field of migration.